Characteristics and risk factors for Pneumocystis jirovecii pneumonia in patients with idiopathic membranous nephropathy - Yang, Lie; Xia, Peng; Zhou, Yangzhong; Cui, Quexuan; Chen, Gang; Zheng, Ke; Qin, Yan; Li, Xuemei (European journal of clinical microbiology & infectious diseases, 2021)
Pneumocystis jirovecii pneumonia (PCP) is a life-threatening opportunistic infection in idiopathic membranous nephropathy (IMN) patients, who are treated with immunosuppressive drugs. However, the risk factors of infection and their prognosis are rarely investigated. We aimed to characterize the clinical manifestations of PCP in patients with IMN, and to understand their risk factors, so that we can provide early warnings to patients with high risk and potential poor prognosis. We conducted a retrospective observational study of IMN patients in a referral center in China, from Jan 2012 to Dec 2018. Clinical and laboratory data were collected separately at the time of IMN and PCP diagnosis. Patients with PCP were matched to those without by gender and age at a ratio of 1:4. The risk factors and prognostic factors were determined by univariate and multivariate logistic regression analysis. A total of 879 patients with IMN were included, with a median follow-up of 267 (interquartile range (IQR) 64,842) days. In total, 26 (2.96%) of them were diagnosed with PCP. The infection rate increased to 3.87% among patients who received corticosteroids, and it further increased to 5.49% in those received over 0.5mg/kg prednisone. Univariate analysis indicated that initial usage of corticosteroids, use of cyclophosphamide, reduced estimated glomerular filtration rate (eGFR), and higher 24-h proteinuria were related to the PCP susceptibility. Multivariate analysis revealed that corticosteroid treatment and reduced eGFR increased the risk of the Pneumocystis jirovecii infection. The case fatality rate of the PCP patients was 23.08%, and increased to 75% among patients requiring invasive ventilation. Univariate analysis indicated that pulmonary insufficiency, invasive ventilation, decreased eGFR, and increased lactate dehydrogenase at presentation were linked to poor prognosis. PCP is not rare in patients with IMN, especially those on corticosteroids, and presented with decreased eGFR. Considering the high case fatality rate, further studies are in need for prevention and management of these patients.